Impact of Lipoprotein(a) Level on Low-Density Lipoprotein Cholesterol– or Apolipoprotein B–Related Risk of Coronary Heart Disease - Arnold, Natalie, MD; Blaum, Christopher, MD; Goßling, Alina, MSc; Brunner, Fabian J., MD; Bay, Benjamin, MD; Zeller, Tanja, PhD; Ferrario, Marco M., MD, PhD; Brambilla, Paolo, MD; Cesana, Giancarlo, PhD; Leoni, Valerio, MD; Palmieri, Luigi, PhD; Donfrancesco, Chiara, PhD; et al. (Journal of the American College of Cardiology, 2024)
AbstractBackgroundConventional low-density lipoprotein cholesterol (LDL-C) quantification includes cholesterol attributable to lipoprotein(a) (Lp(a)-C) due to their overlapping densities. ObjectivesThe purposes of this study were to compare the association between LDL-C and LDL-C corrected for Lp(a)-C (LDL Lp(a)corr) with incident coronary heart disease (CHD) in the general population and to investigate whether concomitant Lp(a) values influence the association of LDL-C or apolipoprotein B (apoB) with coronary events. MethodsAmong 68,748 CHD-free subjects at baseline LDL Lp(a)corr was calculated as “LDL-C—Lp(a)-C,” where Lp(a)-C was 30% or 17.3% of total Lp(a) mass. Fine and Gray competing risk-adjusted models were applied for the association between the outcome incident CHD and: 1) LDL-C and LDL Lp(a)corr in the total sample; and 2) LDL-C and apoB after stratification by Lp(a) mass (≥/<90th percentile). ResultsSimilar risk estimates for incident CHD were found for LDL-C and LDL-C Lp(a) corr30 or LDL-C Lp(a) corr17.3 (subdistribution HR with 95% CI) were 2.73 (95% CI: 2.34-3.20) vs 2.51 (95% CI: 2.15-2.93) vs 2.64 (95% CI: 2.26-3.10), respectively (top vs bottom fifth; fully adjusted models). Categorization by Lp(a) mass resulted in higher subdistribution HRs for uncorrected LDL-C and incident CHD at Lp(a) ≥90th percentile (4.38 [95% CI: 2.08-9.22]) vs 2.60 [95% CI: 2.21-3.07]) at Lp(a) <90th percentile (top vs bottom fifth; Pinteraction0.39). In contrast, apoB risk estimates were lower in subjects with higher Lp(a) mass (2.43 [95% CI: 1.34-4.40]) than in Lp(a) <90th percentile (3.34 [95% CI: 2.78-4.01]) ( Pinteraction0.49). ConclusionsCorrection of LDL-C for its Lp(a)-C content provided no meaningful information on CHD-risk estimation at the population level. Simple categorization of Lp(a) mass (≥/<90th percentile) influenced the association between LDL-C or apoB with future CHD mostly at higher Lp(a) levels.